2010
DOI: 10.1007/s11802-010-1693-1
|View full text |Cite
|
Sign up to set email alerts
|

The toxic mechanism of high lethality of herbicide butachlor in marine flatfish flounder, Paralichthys olivaceus

Abstract: The toxic mechanism of herbicide butachlor to induce extremely high lethality in marine flatfish flounder, Paralichthys Olivaceus, was analyzed by histopathological examination, antioxidant enzymes activities and ATP content assay. Histopathological examination of gill, liver and kidney of exposed fishes showed that gill was a target organ of butachlor. The butachlor seriously impaired the respiration of gills by a series of lesions such as edema, lifting and detachment of lamellar epithelium, breakdown of pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
(19 reference statements)
1
6
1
Order By: Relevance
“…Our results show that the kidneys of rainbow trout can be damaged by toxic concentrations of butachlor. However, in contrast to our study, Guo et al ( 2010) found that acute exposure to butachlor induced a marked dysfunction in gills, but not the liver and kidneys of flounder (Paralichthys olivaceus).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results show that the kidneys of rainbow trout can be damaged by toxic concentrations of butachlor. However, in contrast to our study, Guo et al ( 2010) found that acute exposure to butachlor induced a marked dysfunction in gills, but not the liver and kidneys of flounder (Paralichthys olivaceus).…”
Section: Discussioncontrasting
confidence: 99%
“…The remnants of the pesticide can enter ground waters used for human consumption and thus can be potentially hazardous for human health (Yu et al 2003). The severe effects of the herbicide on many animals have been reported and include retardation of growth and reproduction in earthworms (Eisenia fetida) (Muthukaruppan and Gunasekaran 2010), damage to epithelial tissue in E. fetida (Muthukaruppan et al 2005), neurotoxicity in land snails (Rajyalakshmi et al 1996), genotoxicity in toads, frog tadpoles and fishes (Ateeq et al 2006;Yin et al 2008;Guo et al 2010), while it acts as an indirect mutagen in hamsters and rats (Hsu et al 2005). The 96h LC 50 for the acute toxicity of butachlor in fish varies from 0.14 to 0.52 mg/l and its rate for rainbow trout (Oncorhynchus mykiss) has been reported to be 0.52 mg/l, showing its high toxicity in fish (Tomlin 1994).…”
mentioning
confidence: 99%
“…One of the reasons for this might be due to the barrier function formed by the complexation between HP-β-CD and butachlor. The mechanisms of butachlor on fish mainly including the dysfunction of gill respiration, the generation of oxidative stress, and biochemical alterations . Many studies in the literature have reported the sustained release characteristics of inclusion complex concerning CDs. , In butachlor/HP-β-CD inclusion complex and butachlor technical exposure groups, the concentration of free butachlor in the former group was lower, so tested fishes contacted less butachlor.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons for this might be due to the barrier function formed by the complexation between HP-β-CD and butachlor. The mechanisms of butachlor on fish mainly including the dysfunction of gill respiration, the generation of oxidative stress, 43 and biochemical alterations. 10 Many studies in the literature have reported the sustained release characteristics of inclusion complex concerning CDs.…”
Section: Soil Mobility Studymentioning
confidence: 99%
“…LC 50 (96 h) of butachlor in fishes has been reported to range from 0.14 to 0.52 mg/L (0.52 mg/L in rainbow trout, Oncorhynchus mykiss (Tomlin, 1994). Many adverse effects of this herbicide on fish species have been reported (Lasheidani et al, 2008;Guo et al, 2010;Tu et al, 2013;Zhu et al, 2014;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%